2011
DOI: 10.1021/ja1093309
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(II)-Catalyzed Enantioselective C−H Functionalization of Indoles

Abstract: A catalytic, enantioselective method for the C-H functionalization of indoles by diazo compounds has been achieved. With catalytic amounts of Rh 2 (S-NTTL) 4 , the putative Rh-carbene intermediates from α-alkyl-α-diazoesters react with indoles at C(3) to provide α-alkyl-α-indolylacetates in high yield and enantioselectivity. From DFT calculations, a mechanism is proposed that involves a Rh-ylide intermediate with oxocarbenium character.Indoles are important structural motifs in a myriad of biologically interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(93 citation statements)
references
References 40 publications
3
90
0
Order By: Relevance
“…3c). Coordination of methanol at this site is clearly feasible (as indeed related complexes have featured, acetonitrile, ethyl acetate and tetrahydrofuran, for example [13][14][15] ).…”
Section: -15mentioning
confidence: 99%
“…3c). Coordination of methanol at this site is clearly feasible (as indeed related complexes have featured, acetonitrile, ethyl acetate and tetrahydrofuran, for example [13][14][15] ).…”
Section: -15mentioning
confidence: 99%
“…21 Fox and co-workers found that the reactions of the α-alkyl-α-diazoesters with indoles catalyzed by the Rh 2 (S-NTTL) 4 could afford the C−H insertion products with high yield and enantioselectivity (ee value up to 99%). 16 Apparently, this cannot be explained by the mechanism proposed by Davies. 14 By contrast, Fox suggested that the nucleophilic attack of indole at carbene should involve the concerted formations of C−C and C−O bonds first to give oxocarbenium ylide 8 followed by a [1,2]-H shift to complete the catalytic cycle.…”
Section: Introductionmentioning
confidence: 97%
“…16−20 For instance, Davies's [3 + 2] annulation of indoles with styryldiazoacetates could give the fused indolines with an ee value up to 98%; 14 Barluenga et al reported an asymmetric C2−C3 cyclopentannulation of 2-substituted indoles with Fischer carbenes; 15 Fox et al described a general Rh-catalyzed method for the enantioselective C−H insertion of indole into the α-alkyl-α-diazoesters. 16 However, despite the great successes in this field, the related reaction mechanisms are not quite clear, especially, for the Rh(II)-catalyzed C−H insertion reaction of indole. The reason could be partly attributed to the difficulties in determining the active intermediates experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Although several catalysts including rhodium, copper, and ruthenium have been developed for the C À H functionalization of indoles in the past decades, [7] only quite recently was a highly enantioselective C À H functionalization of indoles disclosed by Fox and co-workers. [8] With catalytic amounts of [Rh 2 A C H T U N G T R E N N U N G (S-NTTL) 4 ] {dirhodium(II) tetrakis[N-(1,8-naphthaloyl)-(S)-tert-leucinate]}, the aalkyl-a-diazoesters reacted with indoles at C-3 to produce a-alkyl-a-indolylacetates in high yields and high enantioselectivities (79-99% ee). From a synthetic point of view, the indole functionalization with a-aryla-diazoesters is a very useful reaction for the construction of a-aryl-a-indolylacetates, which are key intermediates for the synthesis of a wide range of bioactive compounds.…”
Section: A C H T U N G T R E N N U N G (S-pttl)mentioning
confidence: 99%